PEMAKNAAN PENGGEMAR K-POP INDONESIA DI BAWAH UMUR TERHADAP VIDEO MUSIK BIGBANG R-RATED - Nurul Hidayah; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2019)
This research discuss how Indonesian underage K-Pop fans interprets of BIGBANG’s Bae Bae music video. BIGBANG Bae Bae music video get label 19 (R-Rated) and is not allowed to air on music program on one of Korea's national television. However, this music video is not age-restricted and can be easily accessed by Indonesian fans on Youtube. BIGBANG has leaked the concept of its music video specifically for audiences 19 years and older. The aim of this research is to find out Indonesian underage K-Pop Fans Reception of BIGBANG R-Rated Music Video. This research uses Roland Barthes's semiotic analysis to determine the preferred reading and Stuart Hall's reception analysis to find the audiences reception category in dominant, negotiated, or oppositional. The research results showed that most informants interpreted Bae Bae's music video in a negotiated reading. This is because of the three informants have interpreted the music video in accordance with the preferred reading. However, there are other messages that are interpreted based on the personal opinions of each informant after finding out from the lyrics of the Bae Bae song and the contents of the music video story as well as their assumption about the music video in question is the work of art from music makers.